Teaching and Learning Strategies in English as a Medium of Instruction Classrooms for the Deaf Students: A Case of Njombe Secondary School for the Deaf in Tanzania - Peter Kayombo; Gabriel Walubita (Indonesian Educational Research Journal, 2026)
The utilisation of English as a Medium of Instruction in the Deaf education presents a significant challenge in linguistic communication and pedagogy, especially in the situations when the main mode of communication is the sign language. This paper explores teaching strategies used by teachers and learning strategies employed by Deaf students in Tanzania secondary school classrooms where English is used as a medium of instruction. The study employed qualitative case-study design to generate in-depth information from teachers and students at Njombe secondary school for the deaf, it was grounded on Vygotsky’s Sociocultural Theory that emphasize social-interaction in learning. Purposive sampling was used to select 25 participants including 10 teachers and 15 Deaf students who formed three groups with assistance of Sign Language Interpreters. Thematic analysis was used to analyse data collected through interview, Focus group discussion and classroom observation. The results indicate that teachers and students have various adaptive strategies; code-switching between English, Kiswahili, and Tanzania Sign Language; visual-aids and gestures; collaborative learning; and utilising technology to address communication challenges in English Medium classrooms. The paper concludes that successful learning through English as Medium of Instruction in classrooms with Deaf learners attached on bilingual and multi-modal structured pedagogies instead of using English alone. Therefore, results highlight the necessity to make the sign language as official component in the English Medium of Instruction practice to provide equal opportunities to access, meaningful involvement and deeper learning. Finally, the paper suggests to adopt a clear policy of deaf education through bilingual education